2005
DOI: 10.1007/s11167-005-0471-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Polycondensation of Betulin with Adipic Acid

Abstract: The influence of various factors on the kinetics of polycondensation of betulin (a triterpene alcohol of the lupane series) with adipic acid was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…Comparing the difference between the relative amounts of protons calculated by the integration of peaks of primary alcohol (∼1) and secondary alcohol (∼0.25) revealed that primary alcohol was replaced much more than secondary alcohol. In fact, primary alcohol is about 5 times more reactive than secondary alcohol (Nemilov et al, 2005). Therefore, betulin underwent a substitution first on its primary alcohol and then on its secondary alcohol.…”
Section: Nmr Analysismentioning
confidence: 99%
“…Comparing the difference between the relative amounts of protons calculated by the integration of peaks of primary alcohol (∼1) and secondary alcohol (∼0.25) revealed that primary alcohol was replaced much more than secondary alcohol. In fact, primary alcohol is about 5 times more reactive than secondary alcohol (Nemilov et al, 2005). Therefore, betulin underwent a substitution first on its primary alcohol and then on its secondary alcohol.…”
Section: Nmr Analysismentioning
confidence: 99%
“…The experimental search for growing length scales uses many different observables, it has been going on for several decades 2,3 and it is an ongoing active field of research [4][5][6] , but there is still no clear conclusion. Another approach is advocated by the so-called elastic models, the main ideas of which date back to a paper by Eyring and co-workers from 1943 7 and Nemilov's further work in 1968 8 . These models relate the activation energy to the viscous liquid's short-time elastic properties 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The non-Arrhenius behavior of glass-forming liquids is no exception. Classical phenomenological models relate the relaxation time to macroscopic liquid properties, like the configurational entropy [22,23], the free volume [24,25,26,27], the energy [6,17,28,29,30,31,32], or the high-frequency elastic constants [33,34,35,36,37]. More recently, these models were supplemented by theories that generally have a more fundamental basis like, e.g., the mode coupling theory [13,38], the random-first-order-transition theory (RFOT) [39,40], energy-landscape based models [41,42,43,44,45], frustration-based approaches [46], the entropic barrier hopping theory [47], kinetically constrained models [48,49], etc.…”
Section: Introductionmentioning
confidence: 99%